Analisis Pendapatan Usaha Pengolahan Ikan Asin pada Usaha Rumah Tangga di Bontang Kuala, Kalimantan Timur - Kurniawan A., Erwin; Hasid, Zamruddin; Busari, Arfiah (Jurnal Galung Tropika, 2023)
Indonesia is an archipelagic nation known as a maritime area with natural riches in fisheries, such as marine biota and marine tourism. Since 1952, the progress of Bontang Kuala City has been supported by various industrial centers that utilize fishery products. This study aims to study financial aspects, including income, expenses, efficiency, and profits in the salted fish processing business managed by residents who live around the coastal area of Bontang City. The instruments applied to analyze data are analysis of business efficiency, costs, revenues, and profits. The objectivity of the study relies on the method of direct interviews with informants. The study results show that the average fixed and variable monthly costs, average revenue, and average monthly profit are "very efficient." Even though the RCR in the salted fish processing business in Bontang Kuala is classified as "efficient", obstacles still lead to entrepreneurs' prosperity and the allocation of supporting equipment. The implications of the findings are discussed and explored in subsequent publications. The study's results also inspire and dedicate significant contributions to the direction of more adaptive stakeholder regulations in the future.